Traditional food consumption pattern and nutritional status of Oraons: An Asian Indian indigenous community - Bisai, Samiran; Dutta, Sarnali; Das Mohapatra, Pradeep K. (Frontiers in Sustainable Food Systems, 2023)
Introduction Food consumption is an intensive social activity and can be considered a cultural artifact, reflecting the intricate process of sociocultural differentiation in shaping eating habits. Food has a positive effect on a person's health, physical performance, and state of mind. The nutritional composition of a person's diet plays a significant role in their overall health and development. Moreover, tribal cuisine is incomplete without a traditional drink. Rice beer, or handia, is one such indigenous alcoholic-fermented beverage that serves as a staple food. Methods This exploratory cross-sectional study was conducted from January, 2018 to December, 2020 to explore the traditional food practices of the Oraon community through a combination of one-to-one interviews, focus group discussions, and measurements. This study also involved the documentation of individual food recipes, from collection to preparation. To assess nutrient intake, we used a 24-h dietary recall method for 200 Oraon families comprising 466 adults and 193 children. Anthropometric measurements, such as body mass index (BMI) for adults and height-for-age and BMI-for-age z-score methods for children, recommended by the WHO, were taken and recorded using standard procedures. Additionally, the nutrient content of handia was analyzed. Results The mean (SD) height, weight, mid-upper arm circumference (MUAC), and BMI of the Oraon people were analyzed. The combined overall prevalence of chronic energy deficiency (CED) (BMI < 18.5 kg/m2) was 39% (37% in men and 40.3% in women). The prevalence of overweight and obesity (BMI ≥ 25.0 kg/m2) was found to be 7.1% among only women. The average daily energy intake was calculated to be 2,290 kcal per capita. It is worth noting that the food and nutrient consumption of the Oraon tribe was largely consistent with the recommended daily allowances/intakes (RDA/RDI). The consumption of root and tuber products was particularly high. The Oraon tribe was found to have a familiar intake of animal protein in the form of meat, including common periwinkles (Littorina littorea). The study also discovered a remarkable array of unique, region-specific festive foods. The consumption of nutrient-rich fermented rice beer was especially noteworthy. Conclusion The present study provides insight into the traditional food practices of the Oraon tribe in West Bengal. It also highlights that their indigenous food consumption patterns have undergone significant changes as a result of admixture with other communities. To address these dietary issues, it is recommended that regional, need-based planning, and effective intervention programs be implemented. To ensure the proper maintenance of the Oraon tribe's traditional food practices, the cultivation of kitchen gardens and the domestication of wild, edible plants, such as seeds and tubers, may be helpful. Moreover, promoting the consumption of macronutrient-fortified handia, an indigenous beverage with high medicinal benefits, could be effective in combating hidden hunger among adults.